2013
DOI: 10.1093/arclin/act004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Hopkins Verbal Test-Revised for Detecting Alzheimer's Disease and Mild Cognitive Impairment in Spanish Population

Abstract: The decline of verbal memory and learning is one of the main symptoms of Alzheimer's disease (AD) and Mild Cognitive Impairment (MCI). The aim of this study was to examine the effectiveness of the Hopkins Verbal Test-Revised (HVLT-R) to discriminate subjects with AD, amnestic MCI (aMCI), and a healthy control group in a Spanish population. Two hundred ninety-eight subjects were assessed with the HVLT-R and the Spanish version of the Mini-Mental State Examination (MEC 35). There were significant differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
9
1
1
Order By: Relevance
“…Similarly, another recent study [11] from New Zealand, which included a cohort of 404 people aged 49-51 years, found that the odds of mild cognitive impairment, as determined by Montreal Cognitive Assessment (MOCA) [54], were twice as high for individuals whose vitamin C levels were below 23 µmol/L (OR 2.1, 95% CI 1.2-3.7, p = 0.01). However, our study results are contrary to an Australian study, which included healthy adults aged 24-96 years and assessed cognitive function by use of a battery of cognitive screening tools: the Modified Mini Mental State Examination (3MS) [55], the Revised Hopkins Verbal Learning Test (HVLT-R) [56], the Symbol Digits Modalities Test (SDMIT) [57] and the Swinburne University Computerised Cognitive Assessment Battery (SUCCAB) [12]. That study found that there was no difference with respect to the diagnosis of major cognitive impairment with 3MS test among patients with adequate or inadequate vitamin C status.…”
Section: Discussioncontrasting
confidence: 86%
“…Similarly, another recent study [11] from New Zealand, which included a cohort of 404 people aged 49-51 years, found that the odds of mild cognitive impairment, as determined by Montreal Cognitive Assessment (MOCA) [54], were twice as high for individuals whose vitamin C levels were below 23 µmol/L (OR 2.1, 95% CI 1.2-3.7, p = 0.01). However, our study results are contrary to an Australian study, which included healthy adults aged 24-96 years and assessed cognitive function by use of a battery of cognitive screening tools: the Modified Mini Mental State Examination (3MS) [55], the Revised Hopkins Verbal Learning Test (HVLT-R) [56], the Symbol Digits Modalities Test (SDMIT) [57] and the Swinburne University Computerised Cognitive Assessment Battery (SUCCAB) [12]. That study found that there was no difference with respect to the diagnosis of major cognitive impairment with 3MS test among patients with adequate or inadequate vitamin C status.…”
Section: Discussioncontrasting
confidence: 86%
“…In accordance with the final score, three levels of cognitive impairment were established: mild (20-24) "MCI", moderate (14-19) "MOCI", and severe (≤14) "SCI". Any score above 24 points indicated the absence cognitive impairment (NCI) (Lobo et al, 1999;González-Palau et al, 2013).…”
Section: Main Outcome Measurementsmentioning
confidence: 99%
“…El âROC se puede interpretar como una medida directa de la capacidad discriminativa de una prueba y por tanto de su utilidad diagnóstica (Altman & Bland, 1994). La prueba informatizada muestra valores muy parecidos a la prueba de referencia de lápiz y papel, en especial en la evaluación de la memoria a largo plazo, reforzando con ello la idea de que el recuerdo diferido o demorado puede discriminar mejor las personas con deterioro cognitivo o demencia, mostrando una alta utilidad clínica (González-Palau et al, 2013). Otro estudio también refuerza esta idea, indicando que tomar en cuenta el índice de discriminación en una tarea de recuerdo diferido o a largo plazo representaría una medida útil para distinguir entre personas sin deterioro, de los pacientes con deterioro cognitivo (Russo et al, 2013b).…”
Section: Resultados Y Discusiónunclassified